Effects of Different Types of Cognitive Training on Cognitive Function, Brain Structure, and Driving Safety in Senior Daily Drivers: A Pilot Study - Takayuki Nozawa; Yasuyuki Taki; Akitake Kanno; Yoritaka Akimoto; Mizuki Ihara; Ryoichi Yokoyama; Yuka Kotozaki; Rui Nouchi; Atsushi Sekiguchi; Hikaru Takeuchi; Carlos Makoto Miyauchi; Takeshi Ogawa; et al. (Behavioural Neurology)
Background. Increasing proportion of the elderly in the driving population raises the importance of assuring their safety. We explored the effects of three different types of cognitive training on the cognitive function, brain structure, and driving safety of the elderly. Methods. Thirty-seven healthy elderly daily drivers were randomly assigned to one of three training groups: Group V trained in a vehicle with a newly developed onboard cognitive training program, Group P trained with a similar program but on a personal computer, and Group C trained to solve a crossword puzzle. Before and after the 8-week training period, they underwent neuropsychological tests, structural brain magnetic resonance imaging, and driving safety tests. Results. For cognitive function, only Group V showed significant improvements in processing speed and working memory. For driving safety, Group V showed significant improvements both in the driving aptitude test and in the on-road evaluations. Group P showed no significant improvements in either test, and Group C showed significant improvements in the driving aptitude but not in the on-road evaluations. Conclusion. The results support the effectiveness of the onboard training program in enhancing the elderly’s abilities to drive safely and the potential advantages of a multimodal training approach.